Comunicação midiática e consumo de afetos : narrativas sobre protestos e ocupações contra a Reorganização Escolar em São Paulo - Rico, Omar Alejandro Sánchez (2017)
The understanding of a journalistic narrative does not obey only rules strictly rational or logical. It is a product of the affections that the reader experiences from the stimuli that the imago-textual message provides. On the assumption that companies are organized in sharing of sensibilities in flux, we organize our theoretical object under the three-pronged perspective: that of the affections mobilized in the consumers of media narratives independent; the narrative of a social event through the enunciative action of the media independent; and the processes of subjectivation of individuals and collectivities in the state of social protest. To answer these questions, we use as theoretical apparatus a between the understanding of Marilena Chaui, Vladimir Safatle and Muniz Sodré about affections in the information media; the notion of narrative proposed by Michel de Certeau; and narrative identity of Paul Ricoeur; the double concept of politics and police proposed by Jacques Rancière; with the authors Oscar Aguilera and Rose de Melo Rocha We discuss concepts related to the political and aesthetic function within the informative narratives of violence during acts of social mobilization. We work with the empirical object of representations produced during demonstrations against the School Reorganization of the state of São Paulo, in the year 2015. From this social In particular, it is important to discuss the narrative identity of scenes of violence among students and the military police of the State of São Paulo, when independent online media. In this way, we inquire about the emotional basis of communication, from which the idea of ​​a self-reflective subject emerges.